2017
DOI: 10.3892/mmr.2017.6628
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-fibrotic effect of Sedum sarmentosum Bunge extract in kidneys via the hedgehog signaling pathway

Abstract: Sedum sarmentosum Bunge (SSBE) is a perennial plant widely distributed in Asian countries, and its extract is traditionally used for the treatment of certain inflammatory diseases. Our previous studies demonstrated that SSBE has marked renal anti-fibrotic effects. However, the underlying molecular mechanisms remain to be fully elucidated. The present study identified that SSBE exerts its inhibitory effect on the myofibroblast phenotype and renal fibrosis via the hedgehog signaling pathway in vivo and in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the absence of extracellular osmolytes, E-cadherin, epithelial cell marker, was abundantly localized to the plasma membrane. The expression of α-SMA, a mesenchymal cell marker was rarely detected, which is consistent with previous studies investigating the induction of EMT using NRK-52E cells [ 35 37 ]. When the cells were stimulated by hyperosmotic stress for 12 h, the expression of E-cadherin was markedly decreased, and the expression of α-SMA was dramatically increased in the cytoplasm in a mannitol-dose-dependent manner ( Fig 1A ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the absence of extracellular osmolytes, E-cadherin, epithelial cell marker, was abundantly localized to the plasma membrane. The expression of α-SMA, a mesenchymal cell marker was rarely detected, which is consistent with previous studies investigating the induction of EMT using NRK-52E cells [ 35 37 ]. When the cells were stimulated by hyperosmotic stress for 12 h, the expression of E-cadherin was markedly decreased, and the expression of α-SMA was dramatically increased in the cytoplasm in a mannitol-dose-dependent manner ( Fig 1A ).…”
Section: Resultssupporting
confidence: 91%
“…previous studies investigating the induction of EMT using NRK-52E cells [35][36][37]. When the cells were stimulated by hyperosmotic stress for 12 h, the expression of E-cadherin was markedly decreased, and the expression of α-SMA was dramatically increased in the cytoplasm in a mannitol-dose-dependent manner (Fig 1A).…”
Section: Plos Onementioning
confidence: 65%
“…no. YYR336; Shaanxi Yongyuan Biotechnology Co., Ltd., Shaanxi, China) was extracted in accordance with a previously described method [20]. SSB (82.50% purity) was purchased from Xi'an Yuze Biological Technology Co., Ltd. (Xi'an, China) and identified by Professor Yi Fu at the Department of Pharmacognosy, Yunnan Chinese Medical University.…”
Section: Ssb Extract Preparationmentioning
confidence: 99%
“…Other authors demonstrated that SSBE has marked effects against renal fibrosis (Bai et al, 2014a; Bai et al, 2014b), down-regulating hedgehog signaling pathway (which promotes renal fibrogenesis fostering the formation of myofibroblasts from different cell types through an EMT process). SSBE also reduced the ECM accumulation and angiogenesis (Bai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%